Genommene Kurven : 20 Jahre Edition Staeck. - Riese, Hans-Peter; Gercke, Hans; Heckmanns, Friedrich W.; Staeck, Klaus; Steidl, Gerhard; von Wiese, Stephan; Edition Staeck, Heidelberg; Heidelberger Kunstverein, Heidelberg; Kunstmuseum Düsseldorf (Heidelberg : Edition Staeck, 1985)
Beuys, Joseph ; Kounellis, Jannis ; Palermo, Blinky ; Panamarenko ; Broodthaers, Marcel ; Alfano, Carlo ; Filliou, Robert ; Rainer, Arnulf ; Vautier, Ben ; Böhmler, Claus ; Naegeli, Harald ; Polke, Sigmar ; Becher, Bernd & Hilla ; Heerich, Erwin ; Roth, Dieter ; Minnich, Bernd ; Page, Robin ; Eggenschwiler, Franz ; Schwarz, Reiner ; Schwegler, Fritz ; Schultze, Bernard ; Antes, Horst ; Berner, Bernd ; Knopp, Axel ; Erhardt, Hans Martin ; Pfibyl, Lubomir ; Vostell, Wolf ; etc.
Genommene Kurven : 20 Jahre Edition Staeck, Heidelberger Kunstverein, Heidelberg, 3. Februar bis 17. März 1985 ; Kunstmuseum Düsseldorf, September - Oktober 1985
boek